EP366/#354 The IGCS virtual tumor board in Vietnam: an impact assessment of the last 5 years. (4th December 2022) - Nguyen, Dung; Ng, Joseph; Le, Linda Van; Tran, Quy; Tran, Quynh; Phan, Ngoc; O'Connor, Siobhan; Plotkin, Anna; Han, Aaron; Goodman, Annekathryn; Fujiwara, Keiichi; Jhingran, Anuja; et al.
Abstract : Objectives: To enhance the expertise of local gynecologic oncologists, the International Gynecologic Cancer Society (IGCS) collaborates with Da Nang Oncology Hospital (DOH) in monthly virtual tumor boards using the Project ECHO model. This study evaluates the impact of this collaboration on the diagnosis and treatment of gynecologic malignancy at DOH. Methods: A retrospective review of patients presented at tumor boards from July 2017 to April 2022 was performed. Each tumor board typically consisted of a presentation of two cases with pathology review, a discussion of management, and a short didactic lecture. We report changes in clinical and pathologic diagnoses, treatments, and outcomes. SPSS 20.0 was used for data analysis. Results: 107 cases were presented at 54 tumor boards: 43 ovarian, 23 cervical, 17 uterine, 16 vulvar and vaginal cancers, 4 gestational trophoblastic neoplasia, and 4 other gynecologic diseases. Tumor board discussion changed clinical diagnosis in 15.9%, pathologic diagnosis in 30.8%, and treatment in 74.8% of cases. 103/107 patients agreed with the treatment recommendation, of which 55.3% were completed, 33.0% uncompleted, and 11.7% ongoing. In the completed treatment group, complete response rate was 75.4%, partial response 3.5%, stable disease 1.8%, progressive disease 15.8%, and recurrence 3.5%. The mean duration of treatment delay due to tumor board was 8.9 ± 7.4 days, with 97.2% being less than 4 weeks late. Conclusions: Project ECHO facilitates access by patients in low-middle income countries to best-practice care. Virtual tumor boards improve the diagnosis and treatment of gynecologic cancer patients in low-resource settings without significantly delaying treatment.